3 - Income-Generating Activities in Higher Education: The Case of Kigali Institute of Science, Technology and Management (KIST): Albert Butare - Albert Butare, (Journal of Higher Education in Africa, 2004)
The Kigali Institute of Science, Technology and Management (KIST), Rwanda’s first higher education institution of technology, has taken the lead in entrepreneur- ial activities. In 2002 KIST generated 35 per cent of its budget from its various entrepreneurial activities. By 2008, this figure is projected to surpass 50 per cent. From its inception, it has combined conventional teaching with technology trans- fer initiatives. Particularly successful have been projects involving renewable en- ergies, waste-water management and food-processing. Products developed have included, for example, low-cost hand- and foot-powered water pumps, rainwater- harvesting systems, a crop dryer that uses either sunshine or biomass (such as rice husks, sawdust or firewood), etc. Using feedback from its community develop- ment officers, many of whom are women, KIST has modified simple machines to make them easier for women, trained rural women’s groups in business practices, and trains all of its students in basic business skills. KIST’s Information and Com- munication Technology Centre has become the country’s second biggest Internet service provider, as well as a major supplier of software and computer training. Another income source is providing paid part-time studies for working adults.